From Wall Street to work floor: How private equity buyouts affect workers - Martin Olsson; Joacim Tåg (Research Institute of Industrial Economics (IFN), 2023)
Private equity buyouts have sparked debates among labor unions and worker representatives on how they affect workers. This chapter provides an overview of academic evidence on how private equity buyouts affect workers. We review the theoretical reasons why employees could be affected and then survey the empirical evidence. We point out that significant strides have been made in understanding how private equity buyouts influence workers, with a plethora of studies available for policymakers and practitioners. These studies have found that the impact on workers is not uniform; it varies based on the type of buyout, the nature of workers' roles in the firm before the buyout, and the country's institutional environment. We also highlight a few understudied areas that warrant more attention.
Keywords: G34; J24; J31; L25; M51; 330; Private Equity Buyouts; Restructuring; Wages; Employment; Health; Job Satisfaction